Novel strategies to improve co-fermentation of pentoses with D-glucose by recombinant yeast strains in lignocellulosic hydrolysates - Oreb, Mislav (Landes Bioscience, 2012)
Economically feasible production of second-generation biofuels requires efficient co-fermentation of pentose and hexose sugars in lignocellulosic hydrolysates under very harsh conditions. Baker’s yeast is an excellent, traditionally used ethanol producer but is naturally not able to utilize pentoses. This is due to the lack of pentose-specific transporter proteins and enzymatic reactions. Thus, natural yeast strains must be modified by genetic engineering. Although the construction of various recombinant yeast strains able to ferment pentose sugars has been described during the last two decades, their rates of pentose utilization is still significantly lower than D-glucose fermentation. Moreover, pentoses are only fermented after D-glucose is exhausted, resulting in an uneconomical increase in the fermentation time. In this addendum, we discuss novel approaches to improve utilization of pentoses by development of specific transporters and substrate channeling in enzyme cascades.